Description of Grade V Students' Knowledge of Chewing Fuji Apples Against Plaque Index at Ummi Aida Integrated Islamic Elementary School, Medan Tembung District - sakinah, Permata; Siahaan, Yenny Lisbeth (Journal Dental Health, 2023)
Chewing apples is one way to reduce the plaque index on the teeth, because apples contain vitamins and tannins which function to clean teeth and freshen the mouth which can reduce the formation of plaque on teeth.This research is a descriptive survey study that aims to determine the level of knowledge of students before and after dissemination and to determine their plaque index before and after chewing Fuji apples. This research was conducted on 30 grade V students at Ummi Aida Integrated Islamic Elementary School, Medan Tembung District. Through research, the level of knowledge of students was obtained: before dissemination, 13 people were in good criteria (43.3%), and 17 people were in fair criteria (56.7%); whereas after the dissemination, all respondents (100%) were in good criteria, none were in fair and poor criteria; plaque index before chewing Fuji apples, 22 people in good criteria (73.3%), 6 people in fair criteria (20%), and 2 people in poor criteria (6.7%), while afterwards, 28 in good criteria (93.3%), and 2 people in moderate criteria (6.7%). The conclusion of this study is that chewing apples can reduce the plaque index in school children. In order to maintain dental and oral hygiene, it is expected that students consume fruits rich in fiber such as fuji apples.